Pelaksanaan Desentralisasi Asimteris di Bidang Ekonomi Dalam Perspektif Negara Hukum: - - Arwani Ahmad (CV Rewang Rencang, 2024)
In the administration of regional government, there are symmetrical and asymmetrical regional governments. Regional government with asymmetric decentralization has special characteristics and is different from other regions. This specialty aims to organize effective local government. Effective governance allows the region to maximize its various potentials, where according to the central government's view, both cultural and especially economic potential can be optimized by the region. As times progress and economic development, it is necessary to give certain authorities to regions to maintain the existence of culture and to pay special attention to regions that are centers of economic activity to facilitate the process of transformation of science, innovation and concentration of industry in certain regions. Decentralization is given to provincial regional governments or given to district/city regional governments. The economy is a very important aspect for the region. Because with a healthy economy, regional governments can finance regional government programs for the benefit of the community. Economic progress will be directly proportional to the welfare of the majority of its people. The economic potential possessed by the region includes cultural riches, natural riches, history, industrial areas, trade areas and tourism. According to the author, this potential can be optimized to improve community welfare and also increase income for local governments. With asymmetric decentralization, the region is legally given the authority to carry out regional autonomy in accordance with its potential by bypassing certain restrictions that other regions do not have. Apart from that, because of the central government's plan, developing the region's economic potential can provide stimulus for the surrounding buffer areas.